Smart panel with sweeping and switching piezoelectric patch vibration absorbers: Experimental results - Dal Bo, L.; Gardonio, P.; Casagrande, D.E.; Saggini, S. (Mechanical systems and signal processing, 2019)
•Smart plate equipped with shunted piezoelectric patches for vibration control.•Switching RLC time-varying shunts.•Sweeping RLC time-varying shunts.•Control of multiple resonant modes of a structure.•Blind operation mode without need of system identification. The paper describes the design and development of a smart plate equipped with five piezoelectric patches connected to time-varying RLC shunts. The shunted piezoelectric patches form an array of vibration absorbers, which would normally be tuned to reduce the flexural vibration response of the hosting plate at specific resonance frequencies. In this study, the resistive and inductive components of the shunts are instead either iteratively commuted among given values or periodically varied within given ranges. In this way, the operation frequency of the piezoelectric patch vibration absorbers is either switched over given resonance frequencies or uniformly swept in a given frequency range to produce a broadband control of the flexural vibration response of the hosting plate. This study describes the design and laboratory implementation of the reference fixed tuning and of the proposed switching and sweeping tuning shunts. Also, it provides first experimental evidence of the plate vibration control effects produced by the proposed time varying approaches on the resonant responses of the target flexural modes, which, for the switching operation mode, are comprised between 2.5 and 13.6 dB, whereas for the sweeping operation mode are comprised between 2.1 and 12.5 dB. These are significant results, given that the proposed sweeping operation mode can be operated blindly without need of system identification and thus can effectively work also on structures subject to significant physical variations due to changes in the operating conditions.